Advanced Low‐Flammable Electrolytes for Stable Operation of High‐Voltage Lithium‐Ion Batteries. (29th April 2021) - Jia, Hao; Xu, Yaobin; Zhang, Xianhui; Burton, Sarah D.; Gao, Peiyuan; Matthews, Bethany E.; Engelhard, Mark H.; Han, Kee Sung; Zhong, Lirong; Wang, Chongmin; Xu, Wu
Abstract: Despite being an effective flame retardant, trimethyl phosphate (TMPa ) is generally considered as an unqualified solvent for fabricating electrolytes used in graphite (Gr)‐based lithium‐ion batteries as it readily leads to Gr exfoliation and cell failure. In this work, by adopting the unique solvation structure of localized high‐concentration electrolyte (LHCE) to TMPa and tuning the composition of the solvation sheaths via electrolyte additives, excellent electrochemical performance can be achieved with TMPa ‐based electrolytes in Gr∥LiNi0.8 Mn0.1 Co0.1 O2 cells. After 500 charge/discharge cycles within the voltage range of 2.5–4.4 V, the batteries containing the TMPa ‐based LHCE with a proper additive can achieve a capacity retention of 85.4 %, being significantly higher than cells using a LiPF6 ‐organocarbonates baseline electrolyte (75.2 %). Meanwhile, due to the flame retarding effect of TMPa, TMPa ‐based LHCEs exhibit significantly reduced flammability compared with the conventional LiPF6 ‐organocarbonates electrolyte. Abstract : Advanced low‐flammable electrolytes are developed for high‐voltage lithium‐ion batteries (LIBs). With fluoroethylene carbonate as a proper electrolyte additive, the trimethyl phosphate‐based localized high‐concentration electrolyte achieves greatly extended cycle life over the conventional LiPF6 ‐organocarbonates electrolyte, due to the formation of enhanced surface protection layers, making it a promising candidate for high‐energy‐density LIBs.